2000
DOI: 10.1034/j.1600-0765.2000.035002085.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear leukocyte degranulation induced by leukotoxin from Actinobacillus actinomycetemcomitans

Abstract: The ability of leukotoxin from Actinobacillus actinomycetemcomitans to induce release of lysosomal constituents was studied with human polymorphonuclear leukocytes (PMNL). Leukotoxin purified from A. actinomycetemcomitans or bacterial cells of a leukotoxic strain were mixed with human PMNL and the suspension was incubated under anaerobic conditions. Samples were taken at certain time intervals to examine the cell morphology of PMNL by electron microscopy and the extracellular concentrations of the granule comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 30 publications
6
88
3
Order By: Relevance
“…Johansson et al (25) reported that cells underwent degranulation after LtxA treatment; however, our data do not support this claim because LAMP-1 was never detected on the surface of cells. It is important to note that this group examined the effect of LtxA on total primary peripheral blood mononuclear cells rather than a single cell type.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Johansson et al (25) reported that cells underwent degranulation after LtxA treatment; however, our data do not support this claim because LAMP-1 was never detected on the surface of cells. It is important to note that this group examined the effect of LtxA on total primary peripheral blood mononuclear cells rather than a single cell type.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast, cells that were treated with buffer did not change in appearance or staining properties over time (data not shown). This result could imply a mechanism involving degranulation of the cells, as suggested by Johansson et al (25). Presentation of the lysosomal protein LAMP-1 (CD107a) on the cell surface is characteristic of cellular degranulation (26), but we did not observe cell surface expression of LAMP-1 after LtxA treatment (Fig.…”
Section: Resultscontrasting
confidence: 43%
“…In 2000, Johansson and colleagues (Johansson et al, 2000) reported that LtxA induces rapid degranulation of polymorphonuclear leukocytes prior to lysis of cells. Degranulation is a process that requires actin polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…This property of leukotoxin further supports the importance of electrostatic forces for its association to the bacterial outer membrane. The secreted leukotoxin has been shown to be easily inactivated by environmental proteases and superoxide radicals (Johansson et al, 2000b(Johansson et al, , 2001Balashova et al, 2007). This degradation of the toxin molecule can be inhibited by the presence of superoxide dismutase (SOD) produced by A. actinomycetemcomitans and the naturally occurring protease inhibitors of human serum (Johansson et al, 2001;de Haar et al, 2006;Balashova et al, 2007).…”
Section: Expression and Secretion Of A Actinomycetemcomitans Leukotoxinmentioning
confidence: 99%
“…8). Further analysis of PMNs exposed to leukotoxin showed an extracellular release of proteolytic enzymes from both primary and secondary granules (Johansson 2000b). More over, the interaction between leukotoxin and PMNs mediates activation and release of matrix metalloproteinase 8 (Claesson et al, 2002).…”
Section: Polymorphonuclear Leukocytesmentioning
confidence: 99%